(3eHOC GdCef GdbGfhfi hJWHjbGJg ai GdbVGAjf GdOSJhQi hGdEOGQi GdeUQis - (3eMeO MSf eMeO CMeO CHhYdjh,s; (3LGHQ LGO fUGQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2023)
(3SYi gPG GdHMK Edi GdJYQja HeHOC GdCef GdbGfhfi (B- (3Ch eHOC GdGSJbQGQ GdbGfhfi ceG ojecf JSejJg(B- (3hage eGgjJg agekG cGedkG TGedkG, hYQV GdHfGA GdfXQi ddeHOC YQVkG JaUjdjkG, HOAkG HCUdg GdPi fHJ efg hgh acQI GdCef GdbGfhfi, EP JYQV GdHMK deGgjI acQI GdCef GdbGfhfi cacQI bGfhfjI YGeI(B- (3HGdbOQ GdPi jJWdHg ehVhY GdHMK GdCSGSi hgh age eHOC GdCef GdbGfhfi(B- (3eHjfkG CSGSgG GdacQi hGdadSai, hCgejJgG GdJi LPHJ EdjgG GdacQ GdbGfhfi ai GdYUQ GdMGdi, Hd hLYdJgG eQcRkG dGgJeGe GdabgGA GdbGfhfjjf hGdeDSSGJ GdbVGFjI ai eYXe GdOhd Ef de jcf LejYgG, Ke GLJgO GdHGMK ai GdhUhd Edi JYQja Objb ddacQI hJMOjO TGed dfWGbgG hJWHjbGJgG GdeJfhYI hGdeHGOF GdYOjOI GdeJaQYI efgG, Ke Cced GdHGMK GdYQV GdeNJUQ ddacQI HJJHY fTCJgG JGQjNjkG, heQGMd XghQgG hGdGgJeGe HgG MOjKkG, hecGfJgG ai GdfXe GdbGfhfjI GdJi CNPJ HgG eKd GdfXGe GdbGfhfi GdChQhHi hGdfXGe GdbGfhfi GdCdeGfi hGdfXGe GdbGfhfi GdaQfSi, hWQjbgG GdPi TbJg MJi HdZJ eG gi Ydjg GdBf ef bjeI bGfhfjI YGdjI ai Jdc GdCfXeI(B. (3hHYO GdJYQa Ydi acQI GdCef GdbGfhfi HMSHGfgG CUd GdeHOC hefHYg, JQcR GdHMK Ydi GdEMGWI Heaghe GdeHOC hEjVGM eVehfg EjVGMkG JGekG, JYQjakG hWHjYkI, hHJMOjO YfGUQg hMGdGJg GdJi JTcd fWGb EYeGdg heLGd JWHjbg, ceG CaGV GdHGMK ai JHjGf NUGFU GdeHOC GdJi ejRJg hCKQJ ajg hTcdJ WHjYJg hJWqHYJ HgG JWHjbGJg, hCNjQkG hMJi jcJed HfGA GdeHOC, HSW GdHGMK GdeHGOF GdKdGK GdQFjSjI GdJi jJaQY EdjgG GdeHOC, hGdJi JeKd ai eLehYgG Gdgjcd GdJWHjbi ddeHOC, hgi eHOC YOe QLYjI GdbhGYO GdbGfhfjI heHOC GMJQGe GdeQGcR GdbGfhfjI GdoecJnSHI heHOC GMJQGe GdJhbY GdeTQhY, eSJYQVkG eVehfgG hTQhWgG heYGjjQgG hMGdGJgG heG JJVefg ef bhGYO aQYjI JfOQL ai fWGbgG, hTGQMkG dCKQgG heG Jcadg ef MeGjI dGSJbQGQ GdeQGcR GdbGfhfjI GdaQOjI(B. (3Ke hdjMbb GdHMK ZGjJg GdCSGSjI HEONGd eHOC GdCef GdbGfhfi ai GdfXGe GdbGfhfi GdeUQi, hJMOjOkG ai eLGd GdbVGAjf GdOSJhQi hGdEOGQi, NGV GdHGMK ai CMcGe gPjf GdbVGAjf eJJHYkG heJbUjkG eG MhJg Jdc GdCMcGe ef JWHjb ddeHGOF GdKdGK GdechfI deHOC GdCef GdbGfhfi, djNdU HJMdjdgG HUhQI hGVMI LdjI Yf ehba gPjf GdbVGAjf ef JWHjbGJ eHOC GdCef GdbGfhfi, hRGhjI QDjJgeG dg, hecGfg Hjf Uaha eHGOFgeG, hPdc MJi jecf ai GdfgGjI JHoqjf eG jaJbOg gPGf GdbVGAGf ef JWHjbGJ eHOC GdCef GdbGfhfi, heG jJHbi ef NWi fMh EOeGL GdeHOC ai GdfXGe GdbGfhfi GdeUQi hJbdjOg GdecGfI GdJi jSJMbgG cCMO Cge GdeHGOF GdbGfhfjI GdJi jJCSS YdjgG gPG GdfXGe(B.s
(3CWQhMI (B((3OcJhGQg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdYGe, (B2023s
(3HHdjhLQGajG(B: (3U(B. 387-406.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdYGes; (3eHOC GdGef GdbGfhfjs; (3acQI GdCef GdbGfhfjs; (3eHOC GdeTQhYjIs; (3eHOC YOe QLYjI GdbhGYO GdbGfhfjIs; (3GdeQcR GdbGfhfjs; (3eHOC GMJQGe GdJhbY GdeTQhYs; (3eHOC GMJQGe GdeQGcR GdbGfhfjI GdecJSHIs; (3eHOC YOe QLYjI GdbQGQGJ GdEOGQjIs; (3GdeQGcR GdbGfhfjI GdahQjIs; (3Mb GdJhbY GdeTQhYs; (3GdeQGcR GdbGfhfjI GdeSJeQIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes